La opinión en los periódicos norteamericanos después del 11-S: el derecho a una información discrepante - Martínez Albertos, José Luis (Estudios sobre el Mensaje Periodístico, 2002)
Six months after attack of September 11th, can be studied the consequences of this event from three perspectives: the world-wide repercussion of the fact (the beginning of 21st century), the resurgence in the U.S.A. of a new outbreak of the ideological tendencies more conservatives (the beginning of a new hunting of witches according to the model of McCarthy) and the evidence that a deficit of the right to the information in the American journalism is taking place (the absence of a debate of ideas and self-censure reflected in the fear to express discrepant opinions with respect to the governmental unique thought). Following a Walter Lippmann’ text of 1922, the author of this article thinks that these tensions observed now at USA can produce an ominous result: that the journalism of the USA don’t be able to offer to the citizens a trustworthy image of the society in which they live.
Keywords: Opinion Journalism; journalism in the U; S; A; debate of ideas; McCarthysm